Organizational Transformation through Intrapreneurship: Application of IoT and Poka Yoke in the Peruvian Textile Sector - Paulino-Inga, Maily; Quispe-Tasayco, Corelí; Saenz-Moron, Martin; Straujuma, Anita (LACCEI, 2025)
This study addresses an organizational transformation model guided by intrapreneurship, applied in a Peruvian textile microenterprise with low operational efficiency (63.54%) and unplanned cost overruns equivalent to 8% of sales. The proposal integrates Lean Manufacturing tools with IoT technology, highlighting the implementation of an IoT-supported Poka Yoke system in the cutting area, which reduced defects due to excess layers in the layouts from 60% to 13.64%. This improvement directly contributed to a decrease in the rework rate, which went from 13.34% to 6.3%, strengthening the quality of the final product. At the same time, the standardization of tasks and balancing using the Operator Balance Chart (OBC) improved operational uniformity, reducing non-conformity in cuffs from 10.13% to 7.15% and in collars from 9.31% to 6.22%. Likewise, the application of the 5S methodology and visual management tools optimized the work environment, achieving a reduction in unproductive time spent searching for materials from 23.77% to 9.12%. As a result, operational efficiency increased to 79.70%, approaching the international standards of Colombia (79.12%) and Brazil (80%). The model demonstrates not only its technical effectiveness but also its potential for replication as a sustainable strategy to increase the competitiveness of the Peruvian textile sector.